La violence et la culpabilité en partage : le destin national du thème de l’inceste dans la fiction sud-africaine - Harpin, Tina (Études littéraires africaines, 2014)
Twenty years after the end of Apartheid, violence is still a serious problem in South Africa, despite the prosperity and democratic stability of the state. Sexual violence, in particular, has become a major concern. During the decades of transition, secrets of sexual crimes were disclosed more than ever, and it was made patent that they were intertwined with political violence. Incest thus became a new important fictional theme in South African literature. Actually, the issue was already a tacit burning question for politicians and scientists at the end of the 20th century. Given the racist and eugenist background of the country, incest has long been written in the gothic mode to express White communities’ anxieties, until Doris Lessing, Reza de Wet and Marlene van Niekerk came along. They integrated irony into the gothic and rethought the question of taboo in such a way that it was made available for critical thinking beyond local or racial boundaries. Since the end of the 90s, writing fictions involving incest contributes more than ever to reflect on the possibility or the impossibility of strengthening an extended national community against violence, which I demonstrate through my reading of the novels by Achmat Dangor and of a recent play by Paul Grootboom and Presley Chweneyagae.